1998
DOI: 10.1021/bk-1998-0714.ch002
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Glycoside Precursors to Cabernet Sauvignon and Merlot Aroma

Abstract: Volatile compounds released from Cabernet Sauvignon and Merlot grape glycoside fractions, isolated from both skin and juice, were studied by sensory descriptive analysis and by gas chromatographymass spectrometry (GC-MS). Both acid-and enzyme-hydrolysates were studied. The contribution to wine aroma of the different fractions was evaluated by sensory analysis of white wines to which the hydrolysates had been added. Acid-hydrolysates from each variety increased the intensity of attributes such as tobacco, choco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 0 publications
0
48
0
3
Order By: Relevance
“…While the glycosides often have a bitter taste, they do not contribute to bitterness in wine (Noble et al 1987(Noble et al , 1988. However, upon hydrolysis, the released volatile aroma compounds may affect the aroma profile of a wine, as previously suggested (Wilson et al 1986, Günata et al 1985 and shown (Francis et al 1999). Despite being relatively thermodynamically unstable in the acidic environment of a wine, most glycosides remain intact throughout the winemaking process and, to a lesser extent, in the bottle ).…”
Section: Glycoside Studies In Winementioning
confidence: 75%
“…While the glycosides often have a bitter taste, they do not contribute to bitterness in wine (Noble et al 1987(Noble et al , 1988. However, upon hydrolysis, the released volatile aroma compounds may affect the aroma profile of a wine, as previously suggested (Wilson et al 1986, Günata et al 1985 and shown (Francis et al 1999). Despite being relatively thermodynamically unstable in the acidic environment of a wine, most glycosides remain intact throughout the winemaking process and, to a lesser extent, in the bottle ).…”
Section: Glycoside Studies In Winementioning
confidence: 75%
“…They have been shown to contribute significantly to the dried fig, tobacco, and chocolate aromas in Cabernet Sauvignon and Merlot musts (Francis et al 1998). One of the more interesting grape-derived volatile phenylpropanoids is methyl anthranilate, which is considered to be responsible for the distinctive "foxy" aroma and flavor of the Washington Concord grape (Vitis labrusca) (Wang and De Luca 2005) and may also contribute to the aroma of Pinot noir (Moio and Etievant 1995).…”
Section: Phenylpropanoidsmentioning
confidence: 99%
“…Este fato, em combinação com as condições de demanda evaporativa atmosfé-ricas reinantes, no local e época, levaram à captação, no dossel da cultura, de valores mínimos de potencial da água na folha em -1,3 MPa (Tabela 1 Jackson (1994), dentre outros, mostram que as rotas metabólicas, para o acúmulo da pigmentação fenólica (antocianina, polifenóis totais, taninos), são fortemente influenciadas pela dinâmica da água no solo e pela amplitude térmica. Doravante, Francis et al (1999) comprovaram cientificamente a ligação entre pigmentação fenólica e complexidade do vinho em sabor e aroma.…”
Section: ª Estação De Produção (Cultivo De Inverno)unclassified